Salt intake reduction using umami substance-incorporated food: a secondary analysis of NHANES 2017–2018 data - Shuhei Nomura; Shiori Tanaka; Akifumi Eguchi; Takayuki Kawashima; Haruyo Nakamura; Kaung Suu Lwin; Lisa Yamasaki; Daisuke Yoneoka; Yuta Tanoe; Megumi Adachi; Hitomi Hayabuchi; Shosei Koganemaru; et al. (Public Health Nutrition, 2023)
Abstract